Anterior gradient 2 and 3 – two prototype androgen‐responsive genes transcriptionally upregulated by androgens and by oestrogens in prostate cancer cells. (13th February 2013) - Bu, Huajie; Schweiger, Michal R.; Manke, Thomas; Wunderlich, Andrea; Timmermann, Bernd; Kerick, Martin; Pasqualini, Lorenza; Shehu, Erald; Fuchsberger, Christian; Cato, Andrew C. B.; Klocker, Helmut
<x xml:space="preserve">Abstract</x> Androgens and oestrogens have been implicated in prostatic carcinogenesis and tumour progression. Although the actions of androgens have been studied extensively, the mechanisms underlying oestrogen signalling in prostate cancer are not fully understood. In the present study, we analyzed the effect of androgens and oestrogens on the expression of anterior gradient 2 (AGR2) and anterior gradient 3 (AGR3), comprising two highly‐related genes encoding secretory proteins that are expressed in prostate cancer and one of which (AGR2) has been associated with tumour metastasis. Quantitative reverse‐transcriptase PCR and western blot analysis showed androgen induction of AGR2 and AGR3 in three androgen receptor positive cell lines, starting at concentrations of 0.1 nm. Both AGR genes were also transcriptionally activated by ≥ 5 nm oestradiol but not by isotype selective or nonselective oestrogen receptor agonists in DUCaP cells that harbour a high‐level of wild‐type androgen receptor. A functional androgen receptor but not oestrogen receptor turned out to be required for both androgen and oestrogen regulation. This pattern of androgen and oestrogen regulation was confirmed in VCaP cells and was also observed for FKBP5, a well‐characterized androgen‐regulated gene. Genome‐wide chromatin‐immunoprecipitation studies coupled with deep sequencing identified androgen receptor binding sites localized in the distal promoter and intron regions of the AGR2 and AGR3 genes, respectively. The androgen responsiveness of these enhancers was verified by luciferase reporter gene assays and site‐directed mutagenesis analysis. Androgen treatment also induced p300 and RNA Pol II recruitment to androgen receptor enhancers of AGR2 and initiated local chromatin remodelling and the formation of RNA Pol II‐containing androgen receptor transcription complexes.